The Use of BUKPIN Media on Maintaning Behavior of Dental and Oral Health among Primary School Students - Elmalia Fitri; Annisaa Sittatunnikmah; Ayu Wulandari; Titi Indriyani (Universitas Padjadjaran, 2023)
Dental and oral health are still matter that need serious attention because the biggest problem in society is caries with its prevalence. Public ignorance about dental plaque causes low behavior to maintain dental and oral health. Tooth brushing behavior in children aged 10-14 years is still very low when brushing their teeth at the right time. Interventions in schools that can be carried out to increase children's interest in tooth brushing behavior are through the Smart Book media called BUKPIN, which is a development of oral health education that is oriented to print media by displaying interesting information about dental health for children. Objective: to improve dental and oral health behavior and the degree of dental and oral health in elementary school students. The research was pre-experimental type with the One-Group Pretest-Posttest Design and data collection involving 38 respondents by random sampling from class I–VI students at SD Negeri 5 Jambu, Mlonggo District, Jepara Regency. The results of dental health promotion with BUKPIN media that there was a significant (p-value < 0,005) increase in the aspects of knowledge (0.000), attitude (0.002) and action (0.000). Dental and oral health are influenced by behavioral factors of children's behavior in maintaining dental and oral health. Increased knowledge, attitudes, and actions after the BUKPIN Media intervention prove that oral health education which is oriented to print media by displaying interesting information about dental health has a good influence on dental health maintenance behavior in elementary school children. The BUKPIN Media intervention as the development of dental and oral health education are effective in increasing tooth brushing behavior in elementary school children.Keywords: Oral Health, Elementary School Children, Smart Book Media